Mechatronics and intelligent materials : selected, peer reviewed papers from the 2011 International Conference on Mechatronics and Intelligent Materials (MIM 2011), May 21-22, Lijiang, China - Chen, Ray (Advanced materials research, 2011)
This book brings together 249 peer-reviewed papers on Mechatronics and Intelligent Materials in order to promote the development of those fields by strengthening international academic cooperation and communications, and by exchanging research ideas. It provides readers with a broad overview of the latest advances in the fields of mechatronics and intelligent materials and will be essential reading for those working in those areas. Review from Book News Inc.: The perspective of the conference departs somewhat from the typical because most of the participants were from low and middle income cou.